2018
DOI: 10.1038/s41598-018-31631-y
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of alpha-II-spectrin breakdown products as potential biomarkers for early recognition and severity of aneurysmal subarachnoid hemorrhage

Abstract: This study assessed whether cytoskeletal protein alpha-II spectrin breakdown products (SBDP150, SBDP145, and SBDP120) would identify the presence of aSAH and be associated with severity (GCS score, WFNS grade and survival to hospital discharge). This prospective case-control study, conducted at a tertiary care Level I trauma center, enrolled adult patients with angiography confirmed aSAH who underwent ventriculostomy placement for cerebrospinal fluid (CSF) drainage. There were 40 patients enrolled in the study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Cerebral inflammation, oxidative stress and neuronal apoptosis are involved in the pathogenesis of EBI following SAH (1,2,5,6). Previous clinical studies reported that the 120, 145 and 150 kDa fragments of the 280 kDa neuronal cytoskeletal protein α-II spectrin are elevated in the cerebrospinal fluid of patients with SAH, and revealed that these fragments are potential biomarkers for the severity of aneurysmal SAH (7)(8)(9)(10). A previous experimental SAH study also reported that α-II spectrin fragments were elevated in a rat SAH model (11).…”
Section: Introductionmentioning
confidence: 99%
“…Cerebral inflammation, oxidative stress and neuronal apoptosis are involved in the pathogenesis of EBI following SAH (1,2,5,6). Previous clinical studies reported that the 120, 145 and 150 kDa fragments of the 280 kDa neuronal cytoskeletal protein α-II spectrin are elevated in the cerebrospinal fluid of patients with SAH, and revealed that these fragments are potential biomarkers for the severity of aneurysmal SAH (7)(8)(9)(10). A previous experimental SAH study also reported that α-II spectrin fragments were elevated in a rat SAH model (11).…”
Section: Introductionmentioning
confidence: 99%
“…Compared to intracerebral microdialysis, CSF analysis may reflect a more general picture of brain injury. CSF analysis basing on lumbar puncture is cornerstone for aSAH diagnosis, which means that changes of proteins can be detected quickly and conveniently to clarify the correlation between these changes and SAH pathology (Wasik et al, 2017 ; Papa et al, 2018 ; Kwan et al, 2019 ). To our knowledge, this study is the first to report the change of CSF HSP27 in patients with aSAH as compared with patients with NPH, showing a trend of increasing first and then decreasing in the early days.…”
Section: Discussionmentioning
confidence: 99%
“…Table 1 (Ref. [19][20][21][22][23][24][25][26][27][28][29]) summarizes the degradomic profile of aSAH regarding the prediction of severity and clinical outcome. Degradomics related to vasospasm are summarized in Table 2 (Ref.…”
Section: Degradomicsmentioning
confidence: 99%
“…In [20] enrolled 20 patients with aSAH and 20 controls and found a cutoff level of 2.0 ADU (arbitrary densitometric units) of SBDP150 and a 0.5 ADU of SBDP145 to distinguish between the two groups with sensitivity and specificity of 100%. A cutoff value of 0.5 ADU of SBDP120 was 90% sensitive and 100% specific.…”
Section: Alpha-ii-spectrinmentioning
confidence: 99%
See 1 more Smart Citation